Antioxidant Activity and Cardioprotective Effect of Potentilla reptans L. via Ischemic Preconditioning (IPC) - Ayesheh Enayati; Vahid Khori; Yousef Saeedi; Narguess Yassa* (Iranian Society of Pharmacognosy, 2018)
Background and objectives:  Potentilla reptans L. from Rosaceae family is used as traditional medicine in Iran and other countries. Previous investigations on Potentilla species have reported strong antioxidant activity and cardioprotective effect. In this study, antioxidant activity of aerial parts and root of Potentilla reptans, and the cardio protective role of its root on preconditioning ischemia reperfusion injury have been investigated. Methods: Antioxidant activity of aerial parts and root of this plant were measured by DPPH and FRAP methods and its total phenolics content was estimated by Folin-Ciocalteu assay. Catechin was isolated from ethyl acetate fraction by Paper chromatography. Cardioprotective role of P. reptans root were evaluated by thirty five rats in five groups.The hearts were subjected to 30 minutes of ischemia and 100 minutes of reperfusion. The ischemic preconditioning (IPC) protocol was applied before the main ischemia. The myocardial infarct size was estimated by triphenyltetrazolium chloride (TTC) staining. The hemodynamic parameters, arrhythmia scoring and coronary flow were measured during reperfusion. Results: Potentilla reptans root showed stronger antioxidant activity and total phenolics content compared to the aerial parts. Total extract of root significantly decreased the infarct size and increased coronary flow in a concentration-dependent manner. Conclusion: Our results showed that the protective effects of Potentilla reptans root appeared by its phenolic compounds and reactive oxygen species (ROS) inhibition mechanism.